Transplantation in adults with relapsed/refractory acute lymphoblastic leukemia who are treated with blinatumomab from a phase 3 study. Issue 23 (21st August 2019) - Jabbour, Elias J.; Gökbuget, Nicola; Kantarjian, Hagop M.; Thomas, Xavier; Larson, Richard A.; Yoon, Sung‐Soo; Ghobadi, Armin; Topp, Max S.; Tran, Qui; Franklin, Janet L.; Forman, Stephen J.; Stein, Anthony S.
Abstract : Background: Blinatumomab, a bispecific T‐cell‐engaging (BiTE®) immuno‐oncology therapy, demonstrated superior overall survival versus standard‐of‐care chemotherapy (SOC) in adults with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia (R/R ALL) in the phase 3 TOWER study. Herein, the authors reported clinical features and outcomes for those patients who underwent allogeneic hematopoietic stem cell transplantation (HSCT) after treatment with blinatumomab. Methods: In the TOWER study, adults with R/R ALL were randomized 2:1 to receive blinatumomab or SOC. Study treatment consisted of 2 cycles of induction with blinatumomab or SOC followed by consolidation and maintenance therapy. At any time after the first cycle, patients who were eligible for HSCT could proceed to HSCT. Results: Of the 97 patients who underwent HSCT during the study, baseline characteristics generally were comparable and donor types were similar between the patients treated with blinatumomab (65 patients) and those receiving SOC (32 patients). There was no evidence to suggest that the survival benefit of HSCT differed between the patients treated with blinatumomab and those receiving SOC ( P  = .68). On the basis of descriptive statistics, a survival benefit of HSCT versus no HSCT was not observed in patients who achieved complete remission with full, partial, or incomplete hematologic recovery with blinatumomab (odds ratio, 1.17; 95% CI, 0.54‐2.53). The best outcomes were achieved in patients with no prior salvage therapy and with minimal residual disease response to blinatumomab regardless of on‐study HSCT status. Conclusions: Survival was found to be driven by response to study treatment and by salvage status regardless of on‐study HSCT status. These data should be interpreted with caution because the current study was not designed to prospectively assess survival outcomes associated with HSCT after blinatumomab. Lay Summary: Evidence before this study: Blinatumomab is associated with superior morphologic and molecular response rates and superior overall outcome when compared with standard of care chemotherapy in adults with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia. Added value of this study: The best outcomes with blinatumomab were observed in patients who achieved minimal residual disease remission in first salvage treatment regardless of subsequent allogeneic stem cell transplantation (HSCT). Implications of all the available evidence: Patients achieving CR/CRh/CRi following blinatumomab can have a durable response with or without HSCT. Abstract : Patients with relapsed/refractory B‐cell precursor acute lymphoblastic leukemia who achieve full complete remission (CR), CR with partial hematologic recovery, or CR with incomplete hematologic recovery after treatment with blinatumomab can have a durable response with or without subsequent allogeneic hematopoietic stem cell transplantation (HSCT). In the current study, the best outcomes with blinatumomab are observed among patients who achieved minimal residual disease remission in first salvage therapy regardless of subsequent HSCT.